Experiences of the nursing student in learning HAI prevention and control in Asian countries through the use of scenario-based simulation: an explorative qualitative study - Em, Sovannarith (2024)
Background: Healthcare-associated infections (HAIs) have posed a major threat to both patients and to the safety healthcare personnel worldwide. According to the World Health Organization, 10% of hospitalized patients are affected by HAIs worldwide. Objective: The objective of this study was to explore the experiences of nursing students in learning HAIs prevention and control by the application of the scenario-based simulation pedagogy now in use in two Vietnamese and two Cambodian universities. Methods: A qualitative study was conducted among 160 nursing students from 2 Cambodian universities and 2 Vietnamese universities, and by using the purposive-sampling method. The data were collected through a focus group discussion and analyzed by the Graneheim and Lundman method (Graneheim & Lundman, 2004). Results: Two themes and six categories were generated. 1) First theme: factors for enhancing student learning on the prevention and control of HAIs by use of scenario-based simulation; and 2) Second theme: factors hindering students learning on HAI prevention and control by use of scenario-based simulation. Conclusion: The findings showed that SBS is an effective learning method for nursing students that can be applied to enhance the quality of nursing education in the Asian countries as SBS not only improves the clinical skills, but also the soft skills of nursing students. However, the effective outcomes and impacts can only be achieved in the context with the appropriate learning materials and equipment, simulation facilities and the instructors with pedagogical skills.